“Vidas singulares, estranhos poemas”: um estudo sobre a infâmia em Eneida e Lygia Fagundes Telles - CARMO, Lilian Lobato do (2014)
This work intend to investigate the way that the literature appropriates the social figure of the individual infamous as from the short stories and chronicles present in the books A Estrutura da Bolha de Sabão, by Lygia Fagundes Telles and Aruanda, by Eneida de Moraes, respectively. To think what would qualify infamy, will be used as the guiding concept by of that Michel Foucault, in the essay A Vida dos Homens Infames. What we pretend to show, therefore, is the literary record of the stigma of a subject elsewhere, a figure repelled and excluded from society to escape the control of conventions and even institutionalized by the state laws. Losing the right to physical freedom well as to narrate his own life - this has to be told by clinical records, police reports, or even legal sentences. It is hoped, through this research, to show the way in which literary narratives use social characters of their time also to question the morality and conduct imposed by power devices and authoritarian speech, envisioning thus the literary text as an instrument of social resistance.